Multiple Stent Fractures After Everolimus-Eluting Stent Implantation Causing Acute Myocardial Infarction: A Case Report - Ji, Eun Young (Medicine (Baltimore), 2016)
Stent fracture is an uncommon complication of drug-eluting stent implantation, but it has a clinical significance because of its potential association with adverse cardiac events such as in-stent restenosis, target lesion revascularization, and stent thrombosis. Multiple stent fractures account for a small proportion, but they may lead to more serious complications. Newer generation drug-eluting stents are designed for improved safety and efficacy compared with early generation drug-eluting stents. Multiple stent fractures after newer generation drug-eluting stent implantation are a rare case. We report a case of 25-year-old male who presented with acute myocardial infarction caused by multiple stent fractures after everolimus-eluting stents implantation and was treated by balloon angioplasty. Physicians should be aware of the possibility of multiple stent fractures even after newer generation drug-eluting stent implantation.